The Role Of Electronic Administration In Improving The Financial Performance Of Banks (A Field Study On Public Banks In Lattakia Governorate) - تركمان, حنان; محمد , رامي; الشريف, ياسمين (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to demonstrate the role of electronic management in its dimensions (electronic planning, electronic regulation, electronic control) in improving the financial performance of public banks operating in Lattakia Governorate.أسفل النموذج أعلى النموذجThe researcher followed the descriptive analytical approach in her study, and a group of methods, including relying on secondary and primary data, through a questionnaire that was designed by informing the researcher of the published literature, and it was distributed to (140) respondents, of which (134) were recovered, and (128) were valid questionnaires. For analysis, the research community consisted of a cadre of workers in the departments of the branches of public banks under study, and then the SPSS program was relied on as a tool for analyzing the available data.أسفل النموذج Then the study presented a set of results, including: The banks under study issue periodic financial reports, and the banks disclose changes in obligations, assets and ownership, and electronic management contributes to the design and preparation of the bank’s organizational structure, decision-making by participation, and the multiplicity of power centers within the local banks studying. أسفل النموذج